2000
DOI: 10.1016/s0002-9270(99)00759-5
|View full text |Cite
|
Sign up to set email alerts
|

The long-term reinfection rate and the course of duodenal ulcer disease after eradication of Helicobacter pylori in a developing country

Abstract: OBJECTIVE:The aim of this study was to evaluate the effect of Helicobacter pylori (H. pylori) eradication on the natural history of duodenal ulcer disease and the reinfection rate after treatment in a developing country. METHODS:A total of 111 H. pylori-infected patients with duodenal ulcer were treated with either omeprazole or famotidine plus two antibiotics for 2 wk. Those failed to respond to treatment were retreated with bismuth-based triple therapy. RESULTS:The radication rate was 76% (95% CI: 67-83%). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 10 publications
5
30
1
4
Order By: Relevance
“…It Most of the studies conducted in Bangladesh shown that the eradication rate was between 30-64% [11][12][13] . This is much lower than those obtained in Western countries and the recurrence rate is also higher in our country 14,15 . This low eradication rate in our country may be due to different antimicrobial sensitivity pattern of H. pylori.…”
Section: Introductioncontrasting
confidence: 79%
“…It Most of the studies conducted in Bangladesh shown that the eradication rate was between 30-64% [11][12][13] . This is much lower than those obtained in Western countries and the recurrence rate is also higher in our country 14,15 . This low eradication rate in our country may be due to different antimicrobial sensitivity pattern of H. pylori.…”
Section: Introductioncontrasting
confidence: 79%
“…It is possible that children, when first acquiring the infection, are colonized by multiple H. pylori strains. It has been postulated that over time, through natural selection influenced by host and bacterial factors, one specific H. pylori genotype predominates in infected adults (4,20,23,31). This may be the reason why, in our previous studies, H. pylori-infected children have been found to have greater numbers of organisms compared to infected adults (40).…”
Section: Discussionmentioning
confidence: 73%
“…In these centers, biopsies (ca. 0.1 to 0.2 mg/biopsy) were homogenized under aseptic conditions in either 1.5 ml of sterile saline or transport medium (vial containing 1.5 ml of brucella broth and 20% sterile glycerol) and a loopful of homogenated biopsy tissue streaked onto both nonselective (brain heart infusion [BHI] agar with 5% sheep blood) and selective (Skirrows) media using previously described techniques (31)(32)(33). Briefly, agar plates were placed under microaerobic conditions (5% O 2 , 10% CO 2 , 85% N 2 ) at 37°C and incubated for 5 to 10 days until small, gray, translucent colonies consistent with the morphology of H. pylori were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Un estudio chino sugiere que la gastritis de predominio corporal y OLGIM II-IV se asocian significativamente al riesgo de CG 55 . 56 . En ausencia de AG, el riesgo posterior de CG es tan bajo que no justifica seguimiento 14 , aunque la tasa de reinfección no ha sido bien estudiada en Chile.…”
Section: El Riesgo De Cg Depende De La Presencia De Hunclassified
“…En ausencia de AG, el riesgo posterior de CG es tan bajo que no justifica seguimiento 14 , aunque la tasa de reinfección no ha sido bien estudiada en Chile. Un estudio mostró una tasa de reinfección de 13 ± 4% a 3 años 56 . El efecto de la erradicación de H. pylori sobre la AG y la MI es incierto 57 .…”
Section: El Riesgo De Cg Depende De La Presencia De Hunclassified